How do passive infrared triggered camera traps operate and why does it matter? Breaking down common misconceptions. Issue 2 (June 2016) - Welbourne, Dustin J.; Claridge, Andrew W.; Paull, David J.; Lambert, Andrew
Abstract: The use of passive infrared (PIR) triggered camera traps has dramatically increased in recent decades. Unfortunately, technical descriptions of how PIR triggered camera traps operate have not been sufficiently clear. Descriptions have often been ambiguous or misleading and in several cases are demonstrably wrong. Such descriptions have led to erroneous interpretations of camera trapping data. This short communication clarifies how PIR sensors operate. We clarify how infrared radiation is emitted and transmitted, and we describe the parts of the PIR sensor and how they detect infrared radiation and, by extension, fauna. Several problematic descriptions of PIR sensors are drawn on to highlight flawed descriptions and demonstrate where erroneous interpretations of camera trapping data occurred. By clarifying the language and the description of PIR triggered camera traps, this paper ensures that wildlife researchers and managers using camera traps will avoid flawed interpretations of their data. Avoiding flawed interpretations of data should reduce wasted effort and resources that would otherwise come about as researchers attempt to test flawed hypotheses. Furthermore, this paper provides a thorough technical reference for camera trapping practitioners, which is not present elsewhere in the wildlife research literature. Abstract : Camera traps are a valuable tool for wildlife research. However, understanding how the equipment works is paramount for accurate interpretation of the data. This paper provides a technical explanation of how passive infrared camera traps operate to reduce common misconceptions.